2012
DOI: 10.4102/sajs.v108i1/2.629
|View full text |Cite
|
Sign up to set email alerts
|

The South African National Vegetation Database: History, development, applications, problems and future

Abstract: Southern Africa has been recognised as one of the most interesting and important areas of the world from an ecological and evolutionary point of view. The establishment and development of the National Vegetation Database (NVD) of South Africa enabled South Africa to contribute to environmental planning and conservation management in this floristically unique region. In this paper, we aim to provide an update on the development of the NVD since it was last described, near its inception, more than a decade ago. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…The shaded area indicates those regions where the mean temperature of the wet season is below 22 C (data from Hijmans et al, 2005), the cross-over threshold for C 3 grasses. The distribution of recorded Pooideae grasses is shown Rutherford et al, 2012;SANBI, 2003), and adheres well to the predicted range of C 3 grasses.…”
Section: Introductionsupporting
confidence: 78%
See 2 more Smart Citations
“…The shaded area indicates those regions where the mean temperature of the wet season is below 22 C (data from Hijmans et al, 2005), the cross-over threshold for C 3 grasses. The distribution of recorded Pooideae grasses is shown Rutherford et al, 2012;SANBI, 2003), and adheres well to the predicted range of C 3 grasses.…”
Section: Introductionsupporting
confidence: 78%
“…Burrough et al claim to have found significant percentages (35-85% of the short-cell sum) of Pooideae phytoliths in their samples, including samples dating to the late Holocene (1.4 AE 0.2 ka). There are, however, no Pooideae grasses in Botswana (Field, 1976;Kabelo and Mafokate, 2004;Rutherford et al, 2003Rutherford et al, , 2012SANBI, 2003) (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern plant distributions, obtained from the South African National Botanical Institute (Rutherford et al, 2012;Rutherford et al, 2003;SANBI, 2003), are correlated with AI (Trabucco and Zomer, 2009) and MAT (Hijmans et al, 2005) data to define climatic envelopes for plant species and fit species pdfs (pdf sp ).…”
Section: Climate Reconstruction From Fossil Pollenmentioning
confidence: 99%
“…It must be kept in mind, however, that these taxa are not restricted to the Fynbos Biome. Rather, particularly in the case of Artemisia and Stoebe-type (Stoebe and Elytropappus rhinocerotis) (Urrego et al, 2015), these plants occur across southern Africa where there is enough moisture to meet their requirements, and temperatures during the wet season are below 21°C (Rutherford et al, 2012;Rutherford et al, 2003;SANBI, 2003;Urrego et al, 2015). A temperature depression of 4 -6°C during the last glacial period, as estimated from regional palaeotemperature records (Chevalier and…”
Section: Accepted M Manuscriptmentioning
confidence: 99%